STUDENTS’ ABILITY IN USING ELLIPTICAL CONSTRUCTION AT IKIP MATARAM 2016 - Sri Ariani; Ahmad Hanan (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2017)
The purpose of this research is to describe the second semester students’ ability in using elliptical construction at the second semester students of English Department of IKIP Mataram 2016. Descriptive method is used as the design of this research. This research is indended to analize whether the second semester students of English Department of IKIP Mataram 2016 are able to use elliptical constructions or not and to analize percentage of ability of students in using elliptical constructions. The population of this research is the second semester students of English Department of IKIP Mataram Year 2016 (270 students). The researchers used cluster random sampling to select the sample. The total number of sample is 40 students. Technique of data collection is conducted by using grammar test and questioner. In analyzing the data, the researchers use statistic analysis, refers to descriptive statistic, it is enable the researchers to organize, to summarize, and to describe the observation. Furthermore, in describing the data, the researchers organize the data into frequency distribution. Then, measure the mean scores to find out a single score that can give the indication of the ability of the 40 students on an achievements test. For this purpose, the researchers find out the mean scores. The finding of this study revealed that : (1) The ability of second year students of English Department of IKIP Mataram year 2016 in using elliptical constructions is on low level, it can be seen from the mean score of the students which is 12,1 and this score is on low level. (2) The percentages of qualification for the second year students of English Department of IKIP Mataram year 2016 in using elliptical constructions are on low percentages, it can be seen from the rate percentage of the ability of students in using elliptical constructions. (3) The second semester students of English Department of IKIP Mataram year 2016 able to use elliptical constructions in small number of students. however, most of the students have lack interested about the way lecturer conduct elliptical construction.